SUSTAINABLE ECO-FRIENDLY AGROTOURISM DEVELOPMENT STRATEGY ANALYSIS IN TOMOHON CITY - Liow, Festus Evly Ruben Isak; Boka, Ronald Yusak; Wowiling, Steiva Amerlien Sandra; Poli, Altje Ester; Wantouw, Sonny (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The tourism sector has become a significant contributor to economic growth in various regions, including Tomohon City. The development of the tourism industry, especially the agrotourism sector, has become a trend favored by business actors. To take advantage of this trend, a mature strategy is very important to increase the growth and development of agrotourism in Tomohon City. This study aims to analyze the industry development strategy to encourage sustainable and environmentally friendly agrotourism growth. Quantitative methods based on SWOT analysis and the QSPM method as methods that allow objective evaluation of alternative strategies based on internal and external key success factors. The results of the research reviewed produced a concept for designing agrotourism development in the Agrotourism Area that prioritizes the arrangement and restoration of forest functions to maintain environmental sustainability. By implementing a community empowerment system in agrotourism locations, it will provide benefits to the surrounding community in line with the principles of sustainable tourism development. Its novelty value is by combining an environmentally based agrotourism development strategy by considering elements of local wisdom and the socio-cultural conditions of the community. Furthermore, it has implications for the development of interdisciplinary studies between strategic management, ecotourism, and environmental sustainability, and can be used as a model for similar research in other areas. The ecological implications of this strategy lead to the preservation of agrarian landscapes and local biodiversity, while reducing the pressure on the environment from uncontrolled mass tourism.